Simulation of an electro-hydraulic circuit for ALARS - Duțu, I.C; Axinte, T; Vlăduț, O; Damian, R; Duțu, M.F (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
In this paper, the authors present hydraulic and electro-hydraulic simulations of the circuits needed for ALARS (Automated Launch and Recovery System). In fact, the ALARS is used to launch the side-scan sonar into the sea. First hydraulic circuit has the following devices: tank, filter, fixed displacement pump, check valve, 4/3- way valve with two buttons, throttle valve, pressure relief valve and hand lever valve, tanks reservoir, filter and double acting cylinder (Cy 1-1). Afterwards, second hydraulic circuit has the following devices: pump unit, 4/2-way hand lever valve, throttle valve and two double acting cylinders (Cy 2-1 and Cy 2-2). Forward, the first electro-hydraulic circuit has the following devices: lamp, valve solenoid, pressure relief valve, double acting cylinder (Cy 3-1), throttle valve, 4/2-way solenoid valve, fixed displacement pump, valve displacement pump and tanks. Ultimately, the second electro-hydraulic circuit has the following devices: tank, pump unit, pressure relief valve, double acting cylinders (Cy 4-1 and Cy 4-2), relay, valve solenoid, and lamp.